THE ANATOMICAL EVOLUTION OF INFARCTS OF THE MYOCARDIUM - COSTERO, ISSAC CARLOS (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1950)
In expts on rabbits, a soln of protamine zinc insulin gave a slower but more prolonged action than ordinary insulin, but when used in suspension the action was still slower and even more prolonged
CIENC MEX
Keywords: ANATOMICAL, EVOLUTION, INFARCTS, MYOCARDIUM; MULTIDISCIPLINARIA; MEDICINA INTERNA; CARDIOLOGIA